Quality improvement of clinic flow for complex genetic conditions: Using Ehlers–Danlos syndrome as a model. Issue 6 (26th September 2018) - Prakash, Preeti; Eble, Tanya N.; Dhar, Shweta U.
Abstract: Background: Genetic providers face the challenge of having adequate time to conduct a comprehensive evaluation. Hypermobile Ehlers–Danlos (hEDS) syndrome has a complex array of symptoms. An initial visit can involve approximately 60–80 min and an additional 45 min for the check‐in and checkout process. We propose a model to improve clinic flow and patient satisfaction by using: (a) pre‐appointment questionnaire (b) disease information sheet outlining basic management and (c) itinerary detailing the visit. Methods: New patients were given a questionnaire, an EDS information sheet, and a visit itinerary. In the end, a patient satisfaction survey was administered containing 18 questions pertaining to their satisfaction with the questionnaire, the information sheet, and their overall visit. Completed surveys were turned in to the front desk to maintain anonymity. Results: Based on the survey results, patient satisfaction toward the implementation of a questionnaire was overwhelmingly positive. Survey responders found that the itinerary was added to their understanding of the appointment process and that the hEDS information sheets were helpful, understandable, and appropriate in length. Respondents said that they strongly agreed or agreed with the following statements: (a) I was satisfied with the visit; (b) I now have a better understanding of my condition; (c) This visit was successful in addressing my most pressing concerns; and (d) I would recommend this clinic to others. Conclusion: Designing a disease‐centered model that implements patient‐centered resources improves patient understanding and satisfaction for new hEDS patient visits. This model can be emulated in diagnosis and management of other complex genetic and nongenetic conditions. Abstract : Our manuscript details the utility of a patient itinerary for a chronic medical condition that takes up time and resources in a medical practice. It demonstrates how creating such a process benefits the clinic as much as it does the patient. Ehlers–Danlos syndrome is used as a model to show this quality improvement in clinic flow.